Glutamine and glutamate limit the shortening of action potential duration in anoxia‐challenged rabbit hearts. Issue 9 (2nd September 2015) - Drake, Kenneth J.; Shotwell, Matthew S.; Wikswo, John P.; Sidorov, Veniamin Y.
Abstract In clinical conditions, amino acid supplementation is applied to improve contractile function, minimize ischemia/reperfusion injury, and facilitate postoperative recovery. It has been shown that glutamine enhances myocardial ATP/APD (action potential duration) and glutathione/oxidized glutathione ratios, and can increase hexosamine biosynthesis pathway flux, which is believed to play a role in cardioprotection. Here, we studied the effect of glutamine and glutamate on electrical activity in Langendorff‐perfused rabbit hearts. The hearts were supplied by Tyrode's media with or without 2.5 mmol/L glutamine and 150 μmol/L glutamate, and exposed to two 6‐min anoxias with 20‐min recovery in between. Change in APD was detected using a monophasic action potential probe. A nonlinear mixed‐effects regression technique was used to evaluate the effect of amino acids on APD over the experiment. Typically, the dynamic of APD change encompasses three phases: short transient increase (more prominent in the first episode), slow decrease, and fast increase (starting with the beginning of recovery). The effect of both anoxic challenge and glutamine/glutamate was cumulative, being more pronounced in the second anoxia. The amino acids' protective effect became largest by the end of anoxia – 20.0% (18.9, 95% CI: [2.6 ms, 35.1 ms]), during the first anoxia and 36.6% (27.1, 95% CI: [7.7 ms, 46.6 ms]), during the second. Following the second anoxia, APD difference between control and supplemented hearts progressively increased, attaining 10.8% (13.6, 95% CI: [4.1 ms, 23.1 ms]) at the experiments' end. Our data reveal APD stabilizing and suggest an antiarrhythmic capacity of amino acid supplementation in anoxic/ischemic conditions.